Evaluation of the Bio-Kinetics of Cement Kiln Dust In An Upflow Anaerobic Sludge Blanket Reactor for Treatment of Palm Oil Mill Effluent As A Function of Hydraulic Retention Time - Anwar, Ahmad; Rumana, Ghufran (Elsevier, 2014)
In this paper we operated an upflow anaerobic sludge blanket reactor (UASBR) continuously at 35 °C in order to observe the effects of varying the hydraulic retention time (HRT) from 3.5 to 34.5 d and varying the organic loading rate (OLR) from 1.5 to 46 kg COD m−3 d−1. The pH of the digester improved, which we varied from 1.5 to 14.5 g L−1 CaO-CKD, a range pH 7.5. A high COD degradation rate of 97% and mixed liquor suspended solids (MLVSS) of 99,000 mg L−1 were achieved at an HRT of 24.5 d. The maximum methane yield was 0.346 l CH4/g CODremoved. A CO2 reduction of 87% was obtained at an OLR of 26.5 (r = 0.99). The optimum conditions for digestion of the palm oil mill effluent were determined by studying the bio-kinetics of granulation. The growth yield (YG) was 1.45 g VSS/g CODremoved day; the specific biomass decay (b) was 0.056; the specific biomass growth rate (μmax) was 0.988 d−1; the saturation constant (Ks) was 460; and the critical retention time (Θc) was 2.464 d−1. With a feed flow rate (QF) of 1.65 l/d, the upflow velocity (Vup) was 0.6 m/h, and for a QF of 2.45 l/d, Vup was 0.75 m/h.